Continuous cellulosic bioethanol co-fermentation by immobilized Zymomonas mobilis and suspended Pichia stipitis in a two-stage process. (15th May 2020) - Wirawan, Ferdian; Cheng, Chieh-Lun; Lo, Yung-Chung; Chen, Chun-Yen; Chang, Jo-Shu; Leu, Shao-Yuan; Lee, Duu-Jong
Highlights: Continuous production of bioethanol from pretreated sugarcane bagasse was studied. Continuous separate hydrolysis and co-fermentation process was studied. Simultaneous saccharification and co-fermentation process was compared. Highest yield 0.414 g/g and highest productivity 1.868 g/L/h were separately reported. Abstract: Bioethanol produced from lignocellulosic materials has been considered as one of the most promising fuels to replace fossil fuels. Immobilized yeasts or bacteria have been frequently used in continuous system due to its feasibility for repeated use with high biomass retention during the continuous process. In this study, continuous SHcF (separate hydrolysis and co-fermentation) and SScF (simultaneous saccharification and co-fermentation) were evaluated for ethanol production from alkaline pretreated sugarcane bagasse using Zymomonas mobilis (PVA immobilized cells) and Pichia stipitis (suspended cells). In SHcF fermentation, the ethanol yield and productivity of 0.36 g ethanol/g cellulose (corresponding to 70.65% of theoretical yield) and 1.868 g/L/h were achieved. In contrast, SScF system resulted in an ethanol yield of 0.414 g ethanol/g cellulose (corresponding to 81.17% of theoretical yield) and ethanol productivity of 0.705 g/L/h. The performance of the two systems are compared and discussed.